Pengamanan Kendaraan Roda Dua Berbasis IoT Menggunakan Aplikasi Telegram - Muhammad Rizky Irwansyah; sayuti rahman; Arnes Sembiring (SNASTIKOM, 2022)
In today's modern era, two-wheeled vehicles have become a basic necessity. Almost all people use two-wheeledvehicles for their daily needs. It is easy to use and relatively inexpensive to maintain, which is why many peopleuse it. Along with the increase in the number of two-wheeled vehicles, the crime of theft of two-wheeled vehiclesis also increasing. Therefore we need additional security that is better and more sophisticated on the two-wheeledvehicle itself. One of the technological developments for securing two-wheeled vehicles can now be doneautomatically using Wemos D1 and can be accessed using an Android device, namely telegram. Internet of Things(IoT) is one of the technologies that can be applied to help fulfill the security system. IoT is needed to designsecurity devices on two-wheeled vehicles, by using the telegram application to turn on two-wheeled vehiclesaccording to orders from the owner. LM2596 stepdown is required to lower the motor battery (battery) voltage tosystem voltage. Two-wheeled vehicles that have been installed with this tool can later be turned on or off via thetelegram application and can only be operated by the owner.